Pediatric Emergency Medicine Simulation: Hyperkalemia due to Congenital Adrenal Hyperplasia - Abigail Schuh; Rebekah Burns; Jennifer Reid; Kimberly Stone (Association of American Medical Colleges, 2015)
Abstract Congenital adrenal hyperplasia is a group of autosomal recessive diseases marked by mutation of the genes involved in steroidogenesis. There are many types of the disease with 21-hydroxylase deficiency comprising 90-95% of cases. Medical providers must be able to identify the signs and symptoms of salt-wasting, specifically related to hyperkalemia and hyponatremia. When presented with a critical potassium level, medical providers must rapidly stabilize the cardiac membranes to prevent ventricular arrhythmias. The goal of this scenario is to provide the learner with an opportunity to manage life-threatening pediatric hyperkalemia due to adrenal crisis, where both electrolyte abnormalities and the underlying etiology must be addressed. We include extensive preparatory material to help the instructor prepare the environment and learners. The debriefing tools have been tailored specifically for this scenario, with advice on how the instructor can edit them for different learners. The suggested debriefing comments/questions in the Skill Training section are written in the advocacy-inquiry debriefing style that would best be supported by formative assessment with adequate time for learners to reflect. These are the debriefing questions we use the most in our ongoing educational curriculum. The Medical Management and Teamwork Evaluations/Debriefing Forms are written in the plus/delta debriefing style and are a better fit for summative assessment. We use these less frequently, often as part of our quality improvement work. Because not all the material will be applicable to every instructor and every set of learners, we recommend instructors spend at least 30 minutes of preparatory time with all the materials to ensure familiarity, confidence, and maximal efficacy.